A style of upbringing in urban and rural families. Contrasting preferences of secondary school pupils and their parents - Wąsiński, Arkadiusz; Górniok-Naglik, Alina (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The changes taking place in Polish families, both urban and rural, have become an undeniable fact. They are connected with civilization changes, technical progress and European integration. It results in a transformation of the system of values and norms of social coexistence expressed in a change of a model of upbringing in an urban and rural family. On the one hand, the educational effects depend on using certain educational methods and techniques and, on the other hand, on the type of relationship between parents and children. Therefore, the opinions of secondary school pupils and their parents were taken into account while analysing educational means and methods which describe a certain style of upbringing in a family.
Keywords: parents; values; parenting styles; secondary schools pupils; city; village; life environment